A survey on software defined networking with multiple controllers. (1st February 2018) - Zhang, Yuan; Cui, Lin; Wang, Wei; Zhang, Yuxiang
Abstract: Compared with traditional network, Software Defined Networking (SDN) decouples control plane and data plane, providing programmability to configure the network. In spite of such capability, one of the criticisms of SDN is that the SDN controller is a single point of failure and hence the controller decreases overall network availability. Having multiple controllers improves reliability of the network because the data plane can continue to operate if one controller fails. Furthermore, a single controller of SDN has many limitations on both performance and scalability. Thus, multiple controllers are required and critical for large-scale networks. However, multiple controllers increase network complexity dramatically and impose many new challenges to the management and schedule of SDN. This paper surveys latest researches on multiple controllers of SDN. Benefits and challenges of multiple controllers are discussed after giving an overview of SDN and OpenFlow in the paper. Afterward, we dwell on the detailed design principles and architectures of SDN with multiple controllers. Following that, current research works on multiple controllers placement and scheduling are carefully summarized and analyzed. Finally, we conclude this survey paper with some future works and suggested open research directions.